A prospective audit of a nurse independent prescribing within critical care. Issue 3 (22nd November 2012) - Carberry, Martin; Connelly, Sarah; Murphy, Jennifer
<x xml:space="preserve">Abstract</x> Aims and objectives: To determine the prescribing activity of different staff groups within intensive care unit (ICU) and combined high dependency unit (HDU), namely trainee and consultant medical staff and advanced nurse practitioners in critical care (ANPCC); to determine the number and type of prescription errors; to compare error rates between prescribing groups and to raise awareness of prescribing activity within critical care. Background: The introduction of government legislation has led to the development of non‐medical prescribing roles in acute care. This has facilitated an opportunity for the ANPCC working in critical care to develop a prescribing role. Methods: The audit was performed over 7 days (Monday–Sunday), on rolling days over a 7‐week period in September and October 2011 in three ICUs. All drug entries made on the ICU prescription by the three groups, trainee medical staff, ANPCCs and consultant anaesthetists, were audited once for errors. Data were collected by reviewing all drug entries for errors namely, patient data, drug dose, concentration, rate and frequency, legibility and prescriber signature. A paper data collection tool was used initially; data was later entered onto a Microsoft Access data base. Results: A total of 1418 drug entries were audited from 77 patient prescription Cardexes. Error rates were reported as, 40 errors in 1418 prescriptions (2·8%): ANPCC errors, n = 2 in 388 prescriptions (0·6%); trainee medical staff errors, n = 33 in 984 (3·4%); consultant errors, n = 5 in 73 (6·8%). The error rates were significantly different for different prescribing groups (p < 0·01). Conclusion: This audit shows that prescribing error rates were low (2·8%). Having the lowest error rate, the nurse practitioners are at least as effective as other prescribing groups within this audit, in terms of errors only, in prescribing diligence. National data is required in order to benchmark independent nurse prescribing practice in critical care. Relevance to clinical practice: These findings could be used to inform research and role development within the critical care.